Determinants of Older Adults’ Compliance with Community-Based Elderly Health Post Programs: A Cross-Sectional Study - Sri Astutik Andayani; S. Tauriana; Agung Prasetyo Nugroho (Genius Publishing (CV. Gerbang Ilmu Nusantara), 2026)
Background: Community-based elderly health post programs support preventive care and health monitoring for older adults. However, their effectiveness depends on older adults’ compliance with scheduled activities.Objectives: This study aimed to analyze the determinants of older adults’ compliance with community-based elderly health post programs.Methods: This cross-sectional study included 152 older adults selected using total sampling. Data were collected using structured questionnaires on age, educational level, knowledge, family support, social support, and compliance. Data were analyzed using descriptive statistics, bivariate tests, and binary logistic regression.Results: More than half of the respondents were non-compliant with elderly health post programs (55.9%). Bivariate analysis showed that age, educational level, knowledge, family support, and social support were significantly associated with compliance. In the multivariate model, knowledge emerged as the dominant determinant of compliance (AOR = 29.641; 95% CI = 2.140–410.493; p = 0.011). Social support and age also remained significantly associated with compliance.Conclusions: Knowledge was the strongest determinant of older adults’ compliance with community-based elderly health post programs. Strengthening health education, repeated counselling, and social support from families, cadres, and health workers may improve older adults’ participation and continuity of care.